2000
DOI: 10.1073/pnas.160589697
|View full text |Cite
|
Sign up to set email alerts
|

The role of dynamic palmitoylation in Ca 2+ channel inactivation

Abstract: N-and P͞Q-type Ca 2؉ channels regulate a number of critical physiological processes including synaptic transmission and hormone secretion. These Ca 2؉ channels are multisubunit proteins, consisting of a pore-forming ␣1, and accessory ␤ and ␣2␦ subunits each encoded by multiple genes and splice variants. ␤ subunits alter current amplitude and kinetics. The ␤2a subunit is associated with slowed inactivation, an effect that requires the palmitoylation of two N-terminal cysteine residues in ␤2a. In the current man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 43 publications
2
95
0
Order By: Relevance
“…It is unlikely that the C terminus is involved, because the Ca v 2.2⌬Xba construct was still differentially regulated by the different ␤ subunit isoforms and showed rapid inactivation in the presence of ␤ 3 . The V1 region has been previously implicated in being important for the ␤ 2a subunit-mediated slowing effects on the inactivation characteristics of Ca v 2.1, Ca v 2.3, and Ca v 1.2 calcium channel inactivation (10,(12)(13)(14). However, the ␤ 2a -mediated effects are primarily due to palmitoylation of two cysteine residues in the ␤ 2a V1 region that are present in none of the other ␤ subunits.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that the C terminus is involved, because the Ca v 2.2⌬Xba construct was still differentially regulated by the different ␤ subunit isoforms and showed rapid inactivation in the presence of ␤ 3 . The V1 region has been previously implicated in being important for the ␤ 2a subunit-mediated slowing effects on the inactivation characteristics of Ca v 2.1, Ca v 2.3, and Ca v 1.2 calcium channel inactivation (10,(12)(13)(14). However, the ␤ 2a -mediated effects are primarily due to palmitoylation of two cysteine residues in the ␤ 2a V1 region that are present in none of the other ␤ subunits.…”
Section: Discussionmentioning
confidence: 99%
“…The structural similarity between tunicamycin and palmitoyl CoA led to the finding that tunicamycin can also inhibit protein palmitoylation [36]. Inhibitory effects of tunicamycin on palmitoylation of GAP-43, N-type Ca++ channels, estrogen receptor α variant, and myelin proteolipid protein have been documented [30,[36][37][38].…”
Section: Inhibition Of Protein Palmitoylation Withmentioning
confidence: 99%
“…Mutation of this gene has been found to lead to a phenotype characterized by epilepsy, ataxia, and alterations of calcium currents in cerebellar cells in mice, which is ultimately fatal (Barclay et al, 2001). Although the exact physiological function of CACNA2D2 in nonexcitable cells remains unknown, functional studies of CAC-NA2D2 have revealed that the activity of CACNA2D2 protein may alter the conductance properties of the pore-forming a1 unit as well as their membrane trafficking and, therefore dynamically regulates Ca 2+ current through the VACC (Gao et al, 2000;Hobom et al, 2000;Hurley et al, 2000;Klugbauer et al, 1999). The very frequent and early loss of expression of CACNA2D2 together with a subset of genes in the 3p21.3 homozygous deletion region of human chromosome 3 in human lung and breast cancers suggest a link between the CACNA2D2 and the regulation of proliferation and cell death in lung cancer pathogenesis, possibly through the regulation of the VACC-mediated Ca 2+ influx (Angeloni et al, 2000;Gao et al, 2000;Lerman and Minna, 2000).…”
Section: Activation Of Caspase 3 and Parpmentioning
confidence: 99%
“…Based on the evidence that the activity of CAC-NA2D2 dynamically regulates Ca 2+ currents in L-and T-type calcium channels Gao et al, 2000;Hobom et al, 2000;Hurley et al, 2000), we expected that overexpression of CACNA2D2 might result in an increase in the level of cytosolic Ca 2+ influx. A significant increase in the basal level of the intracellular free Ca 2+ was indeed detected in Ad-CACNA2D2-transduced H460 and A549 cells using (Berridge et al, 1998(Berridge et al, , 2000.…”
Section: Activation Of Caspase 3 and Parpmentioning
confidence: 99%